Effect of low impact exercise in women with Fibromyalgia. A systematic review (Revista Chilena de Rehabilitación y Actividad Física, 2022)
Objectives: To analyze the existing information on the effectiveness of low-impact exercise interventions in people with fibromyalgia. Methodology: Systematic review of the literature by searching PubMed and Scopus. The MEDLINE search terms were High impact aerobics, Fibromyalgia, and Quality of life. The PEDro scale was applied to methodologically evaluate the selected articles. Results: The search in the databases added an average of 403 articles. After applying the inclusion and exclusion criteria, the search was reduced to 11 articles, of which only 7 were analyzed. The type of intervention was diverse, demonstrating the efficacy of exercises in the aquatic environment, taichi, pilates, stretching and exercise with the body itself. Conclusions: The analyzed articles demonstrate the efficacy of performing low-impact exercises for physical improvement and quality of life in people with fibromyalgia and that combined interventions are much more effective.
Keywords: Fibromyalgia; quality of life related to health; physical exercise